Electrical Stimulation to Restore Vestibular Function – Development of a 3-D Vestibular Prosthesis - Della Santina, Charles C. (2005)
Patients who fail to compensate for bilateral loss of vestibular sensory function are disabled by disequilibrium and illusory movement of the visual field during head movement. An implantable prosthesis that restores vestibular sensation could significantly improve quality of life for these patients. To be effective, such a device should encode head rotation in all 3 dimensions. We describe the 3-dimensional angular vestibulo-ocular reflex of normal chinchillas and vestibular-deficient chinchillas undergoing functional electrical stimulation of the vestibular nerve. We also describe the design and fabrication of a head-mounted, 8 electrode vestibular prosthesis that encodes head movement in 3 dimensions.